(untitled) (Journal of Economic Research & Business Administration, 2019)
For a couple of years, the cryptocurrency has made a splash in the world of economy, turning from virtual money into a huge market in its size and creating a new full-fledged ideology of money-crypto-economy. Cryptocurrency has a huge potential for development. Cryptocurrency is a digital currency that uses encryption technology to transfer value over the Internet. But today cryptocurrency is trading that most meets the needs of modern society. This form of currency works independently of the banking system and can use in many countries as cash. The relevance of the study is whether cryptocurrency has a positive impact on the development of the economy. The purpose of this article is studying the impact of the process of introduction and use of cryptocurrencies in the economy of Kazakhstan. This process is intensively developing. The key issue for a deeper understanding of the role cryptocurrency is determining their economic nature. Research methods include the stage of cryptocurrency analysis affecting the financial sector, the dynamics of the cryptocurrency market and the overall analysis of assets. For analysis, we paid attention to five cryptocurrencies with the largest capitalization and a large amount of data. The analysis revealed the main factors affecting the market price of cryptocurrency and ways to eliminate them. In addition, the main problems of introducing cryptocurrencies in Kazakhstan, such as the process of regulation of the cryptocurrency market identified and prospects analyzed. A new form of cryptocurrency uses proposed.